UPAYA PENINGKATAN KREATIVITAS MATEMATIKA SISWA MELALUI MODEL PEMBELAJARAN BERBASIS CONCEPT MIND MAPPING DI SMPN 6 KOTANOPAN SATU ATAP - Benny Sofyan Samosir; Aulia Adi Ratna; Lisna Agustina; Wiwik Novitasari (Jurnal Karya Pendidikan Matematika, 2022)
This research was conducted to determine the increase in students' creativity in learning mathematics through a learning model based on Concept Mind Mapping. This type of research is a classroom action research (PTK). The subjects in this study were students of class VII SMPN 6 Kotanopan Satu Atap. The results of the study after using Mind Mapping learning, namely the results of the first cycle test with a percentage of 41% while the second cycle the percentage of 82,35% increased by 41,35%. The results of the observation of student activity in the first cycle percentage 52,2% while the percentage of the second cycle 67,9% increased by 15,7%. And while the results of the observation of teacher activity in the first cycle the percentage was 55,45%, while the percentage of the second cycle was 81,8%, an increase of 26,35%. And it can be concluded that using a learning model based on Concept Mind Mapping can increase students' creativity in learning mathematics.